Increased serum alkaline phosphatase activity in ankylosing spondylitis. Issue 5 (October 1983) - Sheehan, N J; Slavin, B M; Kind, P R; Mathews, J A
Abstract : Raised serum alkaline phosphatase (AP) levels were found in 13 of 76 patients (17%) with ankylosing spondylitis (AS), and 11 of these 13 underwent further investigation to determine the origin of the increased enzyme activity. Three had levels within the normal reference range on re-estimation, and, of the remaining 8, AP isoenzyme studies indicated an increased liver fraction in 6. Serum gamma-glutamyl transpeptidase (GGT) was raised in only 3 patients. Increased AP activity did not appear to be directly related to disease activity or to drug therapy. These findings confirm the occurrence of increased serum AP activity in AS but challenge a previously reported suggestion that bone is the source of the increased enzyme.